POLA ASUH ANAK SINGLE PARENT DI KELURAHAN BATANG SEROSA KECAMATAN MANDAU - Eva Lasrianita Pangaribuan; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Parenting is a manifestation of the way parents guide their children so that children can respond to the norms and values that exist in society. The purpose of this study is to find out what causes a person to become a single parent and to find out what parenting styles are used by single parents in guiding their children. This study uses role theory with a qualitative descriptive approach and data collection techniques used are observation and interviews using the criteria of research subjects that have been determined. From the results of the study, it can be seen that the cause of a person becoming a single parent is due to divorce and death. The cause of divorce is a cheating spouse and other causes because there is no longer compatibility in the household. Meanwhile, the separation due to death is caused by a spouse who is sick. The parenting pattern used by single parents in Batang Serosa village differs between boys and girls. Single parent girls are stricter in giving different rules than boys, single parents give more freedom because boys tend to rebel more often than girls. Keyword: Parenting, Single Parent